Pesticide exposure and suicidal ideation in rural communities in Zhejiang province, China - Jianmin Zhang; Robert Stewart; Michael Phillips; Qichang Shi; Martin Prince (The World Health Organization, 2009)
OBJECTIVE: To investigate the association between pesticide exposure and suicidal ideation in rural areas of China. METHODS: The analysis involved data from a survey of a representative sample of 9811 rural residents in Zhejiang province who had been asked about the storage of pesticides at home and about whether or not they had considered suicide within the 2 years before the interview. The Chinese version of the 12-item General Health Questionnaire (GHQ) was administered to screen for mental disorder. FINDINGS: The unadjusted odds ratio (OR) for the association between pesticide storage at home and suicidal ideation over the prior 2 years was 2.12 (95% confidence interval, CI: 1.54-2.93). After adjusting for gender, age, education, socioeconomic status, marital status, physical health, family history of suicidal behaviour, GHQ caseness and study design effects, the OR was 1.63 (95% CI: 1.13-2.35). CONCLUSION: A potential marker of chronic pesticide exposure was found to be associated with suicidal ideation, which supports findings from previous studies. Given the high level of pesticide exposure and the high suicide risk in rural China, clarification of the causal mechanisms underlying this association and the development of appropriate interventions are priorities for public health and health policy.